Expert system shell as a variety selection framework for multiple cereal crops - S.N. Islam; Rahul Mishra (Annals of Agricultural Research, 2023)
An Expert System Shell is an interface for strengthening, refining and maintaining the knowledgebase of an Expert System by directly interacting with it. The expert system shell is a complete development environment for developing and maintaining knowledge-based applications and expert systems. Agriculture being a multidisciplinary science there is a scope of developing multiple expert systems for various crops, disease, insects, irrigation scheduling, fertilizer management and various other issues needed for a sustainable agriculture. There has been no such system or software supporting information management in this area that can transform a single expert shell into a multidisciplinary and multi crop expert system. The framework of the shell described in this paper deals with the developmental procedure of multi crop expert system on cereal crops. Cereal grains being a staple food the most important contributor to the world's total food production. They have identical characteristics, growing conditions and agronomic practices that can be accommodated in same framework. The shell takes up the inference engine of the Expert System developed on Wheat crop management.